2020
DOI: 10.1016/j.ntt.2020.106930
|View full text |Cite
|
Sign up to set email alerts
|

Combined vapor exposure to THC and alcohol in pregnant rats: Maternal outcomes and pharmacokinetic effects

Abstract: Cannabis is the most frequently used illicit drug among pregnant women, yet the potential consequences of prenatal cannabis exposure on development are not well understood. Electronic cigarettes have become an increasingly popular route of administration among pregnant women, in part to user's perception that e-cigarettes are a safer route for consuming cannabis products. Importantly, half of pregnant women who consume cannabis also report consuming alcohol, but research investigating co-consumption of these d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 79 publications
13
42
1
Order By: Relevance
“…As demonstrated in our lab ( Breit et al, 2020 ) and others ( Nguyen et al, 2016 ; Javadi-Paydar et al, 2018 ), THC via e-cigarettes lowers core body temperatures in female rats. Maternal body temperatures were measured before and after each vapor exposure session via a rectal thermometer, to verify this expected physiological effect and to examine effects of nicotine exposure on body temperature.…”
Section: Methodssupporting
confidence: 71%
See 3 more Smart Citations
“…As demonstrated in our lab ( Breit et al, 2020 ) and others ( Nguyen et al, 2016 ; Javadi-Paydar et al, 2018 ), THC via e-cigarettes lowers core body temperatures in female rats. Maternal body temperatures were measured before and after each vapor exposure session via a rectal thermometer, to verify this expected physiological effect and to examine effects of nicotine exposure on body temperature.…”
Section: Methodssupporting
confidence: 71%
“…To measure maternal blood levels of each drug and their metabolites, intravenous catheters were surgically implanted prior to pregnancy following a 2-week acclimation period, as previously published ( Breit et al, 2020 ). Dams were anesthetized (4% isoflurane) and the catheter was secured under the skin on the back, with the tubing thread subdermally over the right shoulder and implanted into the right jugular vein via small incisions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…THC inhalation during pregnancy did not alter maternal weight gain or litter size in this study. Only a limited number of studies examined THC inhalation during pregnancy and similarly found no effect of cannabis exposure on maternal weight gain or litter size (Breit et al., 2020; Weimar et al, 2020), but do show reduced birth weight in PCE offspring (Fried, 1976; Weimar et al, 2020). Maternal weight gain and litter size were not examined following THC injection during pregnancy in this study; however, similar to inhalation exposure, previous research found no effect on maternal weight gain or litter size but reduced birth weight in PCE offspring (Natale et al, 2020).…”
Section: Discussionmentioning
confidence: 99%